SOCIOLOGICAL ANALYSIS OF THE ENROLLMENT OF STUDENTS WITH DISABILITIES IN HIGHER EDUCATION BY GENDER AND RACE - Silva, Thayara Rocha; Meletti, Silvia Marcia Ferreira; Lima, Angela Maria de Sousa; Serafim, Jucenir da Silva (Seven Editora, 2025)
This article presents data regarding the enrollment of students with disabilities in Brazilian higher education with a focus on data from Paraná state universities (IEES-PR) and the characterization of these students by race/gender. The data were extracted from INEP (2011-2019), exported using SPSS (Statistical Package for the Social Sciences), and analyzed in light of Sociology. The main objectives were to identify the characterization of these students and to map what the scenario found reveals to us, making it possible to clarify who these subjects are. In general terms, the data reveal many challenges for the access of the black and brown population with disabilities to higher education. In relation to sex, we observe that the national sociological characterization points out that one of the effects of state policy, which does not align the State of Paraná with the national trend, is the greater access of male persons with disabilities than female persons with disabilities. Regarding the type of disability, we observed a higher incidence of physical disability in the national data and in the State of Paraná, followed by low vision. In the state universities of Paraná, we highlight low vision, which makes up 68% of the total enrollments of people with disabilities throughout the entire period. Such data evidence, for example, the need for public policies that contemplate the incentive for a transformation of the scenario of this social reality found, that is, of the social markers that often configure themselves as markers of inequalities and differences.DOI: https://doi.org/10.56238/sevened2025.036-123